Eksistensi Pengurus Terkait Dengan Proses Pemberesan Kekayaan Yayasan Oleh Likuidator Dalam Mewujudkan Kepastian Hukum - Fensky Readel Sumandag; Yuhelson Yuhelson; Bernard Nainggolan (JOURNAL of LEGAL RESEARCH, 2022)
This study investigates the existence of a court-appointed board that serves as a liquidator. When the liquidator conducts the process of settling assets, problems occur if the Foundation's management is unwilling to work with the liquidator. The approach employed in this study is normative legal research, which is conducted in an effort to acquire the pertinent information regarding the issue. The qualitative juridical analysis method is utilized for data analysis. On the basis of Article 63 of the Foundation Law, the results of the study were obtained on the existence of the Management in the process of settling the assets of the Foundation by the liquidator. If the Foundation is dissolved because its time period and objectives have been met or not met, the Trustees appoint a liquidator; if the Trustees do not appoint a liquidator, the management acts as a liquidator; and if the Foundation is dissolved because of a court order, the court also appoints a liquidator. The court-appointed liquidator is authorized to dispose of the Foundation's assets. The nomination of the Management as Liquidator is inappropriate due to the fact that the liquidator is essentially a former member of the Foundation's management, which might cause conflict and impede the process of settling the Foundation's assets.